1993
DOI: 10.1002/polb.1993.090310405
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State 13C‐NMR detection of the isotropic carbonyl line shape in blends of poly(vinylphenol) with main‐chain polyesters

Abstract: The solid‐state NMR isotropic line shape of the carbonyl 13C resonance is useful as a qualitative diagnostic probe of the polyester component′s morphology and molecular mobility in partially miscible blends with poly(vinylphenol), PVPh. The main‐chain polyesters chosen for investigation in this study are poly(ethylene succinate), poly(ethylene adipate), poly(butylene adipate), and poly(caprolactone). A crystalline phase exists for polyester‐rich mixtures in all cases. Verification of this claim is provided by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…Unlike blends of PVPh with various polyesters where specific intermolecular hydrogen-bonding interactions are effective, 19,[22][23][24] there is no such interaction in the PDLLA/PVPh blends. Polymers such as poly(vinyl chloride), 4 poly(hydroxyether of bisphenol-A), 3 polyepichlorohydrin 29 are miscible with aliphatic polyesters having suitable CH x /COO ratios.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Unlike blends of PVPh with various polyesters where specific intermolecular hydrogen-bonding interactions are effective, 19,[22][23][24] there is no such interaction in the PDLLA/PVPh blends. Polymers such as poly(vinyl chloride), 4 poly(hydroxyether of bisphenol-A), 3 polyepichlorohydrin 29 are miscible with aliphatic polyesters having suitable CH x /COO ratios.…”
mentioning
confidence: 89%
“…17,18 Due to the lack of specific interactions, most of these blends are immiscible. Poly(p-vinylphenol) (PVPh) has been found to be miscible or partially miscible with polyacrylates, 19 polymethacrylates, 20,21 and polyesters 19,[22][23][24] on the basis of specific hydrogen-bonding interactions. It has also been found that the interassociation between polymers is affected by the structure of estercontaining polymers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PVPh can also form miscible blends with some aliphatic polyesters (Belfiore, Qin, Ueda, & Pires, 1993;Xing, Dong, An, Feng, Avella, & Martuscelli, 1997;Woo & Chiang, 2004) [e.g., poly(-caprolactone) (PCL), poly(ethylene succinate) (PES), poly(ethylene adipate) (PEA), and poly(␤-hydroxybutyrate) (PHB)], or with some aromatic polyesters (Nurkeeva et al, 2000) [e.g., poly(ethylene terephthalate) (PET), poly(butylene terephthalate) (PBT) and poly(ethylene 2,6-naphthalenedicarboxylate) (PEN)].…”
mentioning
confidence: 99%
“…The hydroxyl groups of PVPh are capable of undergoing intermolecular interactions with proton-accepting functional groups. As a result of such interactions, PVPh is miscible with a large variety of polymers, including polymethacrylates [1][2][3][4][5] , polyacrylates 6) , polyesters [7][8][9][10][11] , polyitaconates 12,13) , polyamides 14) , polyethers 7,15,16) , etheric polyphosphazenes 17) and polyketones 18) . In contrast, not many miscible blends of polyacrylonitrile (PAN) have been reported.…”
Section: Introductionmentioning
confidence: 99%